Protective effects of peptide KSPLY derived from Hericium erinaceus on H2O2-induced oxidative damage in HepG2 cells - Zhengli Xu; Qiuhui Hu; Minhao Xie; Jianhui Liu; Anxiang Su; Hui Xu; Wenjian Yang (Food Science and Human Wellness)
Reactive oxygen species (ROS)-induced oxidative damage is strongly associated with the pathogenesis of chronic diseases, and natural antioxidant peptides have good abilities of scavenging ROS. The antioxidant activity of peptide Lys-Ser-Pro-Leu-Tyr (KSPLY) derived from Hericium erinaceus remains unclear. In the present study, the antioxidant effect and mechanism of KSPLY on H2O2-induced oxidative damage in HepG2 cells were investigated. The results indicated that KSPLY exhibited the antioxidant capacity in H2O2-induced HepG2 cells by enhancing superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) activities. In comparison with the H2O2-treated damage group, the apoptosis rate, ROS level, and malondialdehyde (MDA) content of HepG2 cells treated with KSPLY were significantly decreased. The H. Erinaceus-derived peptide KSPLY pretreatment promoted the expression of detoxification and antioxidant enzymes via the Keap1/Nrf2 signal pathway, thereby inhibiting the generation of ROS and MDA. In conclusion, the H. erinaceus-derived peptide KSPLY effectively protected HepG2 cells against H2O2-induced oxidative damage, and it provided a theoretical basis for the further development of new natural antioxidants.